Staging breast cancer by sentinel lymph node biopsy: Do patients with a single negative sentinel node (N=1) experience worse outcomes than those with multiple negative sentinel nodes (N>1)?. (September 2018) - Wilkerson, Avia; Averbook, Bruce; Joseph, Natalie; Sharpe, Susan; Li, Benjamin
Abstract: Background: Though sentinel lymph node biopsy (SLNB) is standard of care for early breast cancer, concern remains for false negative nodes and potential implications for understaging and under-treatment, particularly when only one sentinel node is retrieved. We examined whether patients with a single negative SLN (N = 1) experience worse survival than those with two or more negative SLNs (N > 1). Methods: This retrospective review examined 730 SLN-negative patients. Clinicopathologic and demographic data, recurrence-free and overall survival were assessed. Statistical analysis included Chi square tests, Kaplan-Meier survival analysis with log-rank tests, and multivariate analysis using the Cox regression model. Results: There were no statistically significant differences in recurrence-free or overall survival between patients in the N = 1 versus the N > 1 group (log rank test, p = 0.75 and p = 0.52, respectively). There were also no differences in local and distant recurrence (1.9% versus 2.1%, p = 0.89 and 2.4% versus 2.3%, p = 0.78) or breast cancer death (2.4% versus 2.7%, p = 0.85). Increased tumor size was associated with finding greater than one negative sentinel node intraoperatively (p = 0.01). Conclusions: A single negative sentinel node did not portend worse recurrence-free or overall survival. After thorough axillary exploration during SLNB, retrieval of a single negative SLN did not result in worse clinical outcomes.